2018
DOI: 10.1021/acs.jced.8b00008
|View full text |Cite
|
Sign up to set email alerts
|

Densities, Viscosities, Speeds of Sound, Bulk Moduli, Surface Tensions, and Flash Points of Binary Mixtures of Ethylcyclohexane or Methylcyclohexane with n-Dodecane or n-Hexadecane at 0.1 MPa

Abstract: This work reports physical property measurements of binary mixtures of ethylcyclohexane or methylcyclohexane with either n-dodecane or n-hexadecane at temperatures ranging from (293.15 to 333.15) K. Mixture densities fell between those of the pure components. All excess molar volumes were positive, indicating less efficient packing in the mixture systems. Mixture speeds of sound fell between those of the pure components, except in ethylcyclohexane in n-dodecane mixtures where increasing the mole fraction of et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 82 publications
(145 reference statements)
4
56
0
Order By: Relevance
“…7−12 These studies have shown the presence of aromatic compounds with 10 carbons. The authors have used n-butylbenzene in the formulation of model mixtures for jet fuel, 6,11 and recent studies have begun to examine important reactions involving other butylbenzene isomers. 13−16 Belisario-Lara and Mebel 13 conducted a computational study to investigate the pyrolysis of n-butylbenzene, sec-butylbenzene, and tert-butylbenzene.…”
Section: Introductionmentioning
confidence: 99%
“…7−12 These studies have shown the presence of aromatic compounds with 10 carbons. The authors have used n-butylbenzene in the formulation of model mixtures for jet fuel, 6,11 and recent studies have begun to examine important reactions involving other butylbenzene isomers. 13−16 Belisario-Lara and Mebel 13 conducted a computational study to investigate the pyrolysis of n-butylbenzene, sec-butylbenzene, and tert-butylbenzene.…”
Section: Introductionmentioning
confidence: 99%
“…One can imagine that a positive excess speed of sound, which indicates a speed of sound that is faster than expected ideally, would come from systems where a closer molecular packing, as indicated by negative excess molar volumes, allows for faster transmission of waves. Some mixture systems have exhibited this behavior, but others have had c E and V m E values that are the same sign (+ or −). , In our recent paper, mixtures of isododecane with propylbenzene, 1,3,5-trimethylbenzene, and 1,2,4-trimethylbenzene had both positive excess speeds of sound and positive excess molar volumes . An additional factor to consider is the mixture’s isentropic compressibility, κ, which is defined in Table along with its ideal value κ ID .…”
Section: Resultsmentioning
confidence: 83%
“…The expansion of the mixtures, as indicated by the positive excess molar volume, might lead one to speculate that the excess speed of sound should be negative because it would take longer to propagate sound through the molecules that are farther apart. Some studies have shown this, but other studies have reported excess speeds of sound and excess molar volumes whose signs (+ or −) were the same. , For example, mixtures of 2,2,4,6,6-pentamethylheptane with n -hexylbenzene had negative excess molar volume with excess speed of sound that was positive. For 2,2,4,6,6-pentamethylheptane with n -butylbenzene, the same trend was seen at low n -butylbenzene concentrations, but at mole fraction greater than 0.5, both excess molar volume and excess speed of sound were positive.…”
Section: Resultsmentioning
confidence: 98%
“…Other physical properties that have been used in surrogate development include density, viscosity, surface tension, flash point, speed of sound, and bulk modulus (see Luning Prak et al 21 and the references herein). 18,21,22 Because of the importance of 1,3,5trimethylbenzene, 1,2,4-trimethylbenzene, and n-propylbenzene in surrogate development, the goal of this work was to measure the thermophysical properties of binary mixtures of these aromatic compounds in 2,2,4,6,6-pentamethylheptane. The densities of 1,3,5-trimethylbenzene, 1,2,4-trimethylbenzene, and n-propylbenzene have been measured in many binary mixtures, with some producing positive and others producing negative excess molar volumes (Tables 1 and 2, eq T1).…”
Section: Introductionmentioning
confidence: 99%